'Employers at the heart of the system': whose system is it anyway? (UCL Press, 2022)
Education and skills policy since the 1970s have exhorted employers to put themselves at the 'heart of the system', to engage voluntarily with colleges and other providers, in a range of roles and activities, some of which may be beyond their competence and experience. However, employers do have an important role to play, but that role should be clearly defined and directed towards those areas where their expertise and experience can be optimally deployed. To function effectively, a system requires partnership between a range of actors - learners, providers, local communities, businesses and voluntary organisations. Contributions and expectations, all of which are important, require coordination and management. It is argued that colleges are well placed to act as 'anchor institutions' for bringing together local partners. This article provides a practical example of how one large general further education college fulfils this role.